1995
DOI: 10.1038/378068a0
|View full text |Cite
|
Sign up to set email alerts
|

A sex difference in the human brain and its relation to transsexuality

Abstract: Transsexuals have the strong feeling, often from childhood onwards, of having been born the wrong sex. The possible psychogenic or biological aetiology of transsexuality has been the subject of debate for many years. Here we show that the volume of the central subdivision of the bed nucleus of the stria terminals (BSTc), a brain area that is essential for sexual behaviour, is larger in men than in women. A female-sized BSTc was found in male-to-female transsexuals. The size of the BSTc was not influenced by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
326
3
38

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 677 publications
(382 citation statements)
references
References 25 publications
15
326
3
38
Order By: Relevance
“…AVT and AVP treatment induces sex-specific reproductive behaviors in a range of vertebrate species, including the spawning reflex in fishes, amplexus in newts, and pair-bonding and parental care in voles (Carter et al, 1995;Egami, 1959;Macey et al, 1974;Moore, 1992). Perhaps the most striking comparison is between our results in fishes, which show a strict correlation between sexual behavior and AVT neurochemistry, and studies showing differences in forebrain peptidergic cell populations in human males who exhibit heterosexual vs homosexual (Swaab and Hofman, 1990) or transsexual (Zhou et al, 1995) behavior.…”
Section: Discussionsupporting
confidence: 62%
“…AVT and AVP treatment induces sex-specific reproductive behaviors in a range of vertebrate species, including the spawning reflex in fishes, amplexus in newts, and pair-bonding and parental care in voles (Carter et al, 1995;Egami, 1959;Macey et al, 1974;Moore, 1992). Perhaps the most striking comparison is between our results in fishes, which show a strict correlation between sexual behavior and AVT neurochemistry, and studies showing differences in forebrain peptidergic cell populations in human males who exhibit heterosexual vs homosexual (Swaab and Hofman, 1990) or transsexual (Zhou et al, 1995) behavior.…”
Section: Discussionsupporting
confidence: 62%
“…Postmortem studies have observed sex-atypical volumes and neuronal numbers in hypothalamic nuclei in the brains of individuals with GD (Garcia-Falgueras and Swaab, 2008;Kruijver et al, 2000;Zhou et al, 1995). Brain structure in individuals with GD has also been investigated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Clear anatomical sex differences have also been described in the human bed nucleus of the stria terminalis (BST). The darkly staining posteromedial component of the BST (BST-dspm) and the central subdivision of the BST (BSTc) are both larger in men than in women (Allen and Gorski, 1990;Zhou et al, 1995;Kruijver et al, 2000). Differences in the size of the human BSTc have been related to the gender identity disorder transsexuality, in which subjects voice the strong feeling of being born in the wrong sex.…”
mentioning
confidence: 99%